Free Trade Agreeement (FTA) in developing and developed countries: in the case of Malaysia-Japan Economic Partnership Agreement (MJEPA) and Malaysia-Pakistan Closer Economic Partnership Agreement (MPCEPA) / Siti Noorfairuz Hamsaruddin - Hamsaruddin, Siti Noorfairuz (2010)
Free trade agreements (FTAs) among developing countries can help them strengthen regional cooperation, but trade treaties between a powerful developed country and developing countries can result in many problems for their consumers, farmers and industries. Malaysia has been engaged in discussions with developed and developing countries towards establishment of Free Trade Area (FTA) arrangements. These arrangements, pursued through bilateral and build upon the commitments under the World Trade Organization (WTO). FTAs provide the means to achieve quicker and higher levels of liberalization that would create effective market access. The main focus of this study is to identify the Free Trade Agreement (FTA) in developed and developing countries: In the case of Malaysia-Japan Economic Partnership Agreement (MJEPA) and Malaysia- Pakistan Closer Economic partnership Agreement (MPCEPA). In addition, Malaysia had signed the FTAs with Japan (developed country) under MJEPA and Pakistan (developing country) under MCPEPA. It will focus on trade in goods, standard and SPS regulations in Japan and Pakistan. Furthermore, some recommendations had been proposed in order to improve the FTA with the developed and developing countries and to strengthen the trading between the countries.